The Possibility of Achieving Iraqi Economic Reform in Light of the Trends of International Institutions - Halah Hashim Kadhim (International Forum of Researchers and Lecturers, 2025)
The research addressed the possibility of achieving economic reform in Iraq based on the directions of the competent international institutions, of which Iraq is a member or observer, as institutions possessing great capabilities and experience accumulated from more than 190 member states in these institutions. It also provides the opportunity for economic cooperation and benefiting from international expertise. For this purpose, it included: The research consisted of three sections, the first section of which dealt with the theoretical framework of economic reform and international institutions, while the second section dealt with the vision of international institutions for economic reform in Iraq, while the third section included the most important conclusions and recommendations reached by the research, which focused on the weak points from which Iraq suffers. The research also recommended a number of points, including the need to benefit from the expertise of these institutions in the economic and social fields in a way that reflects the general interest of Iraqi society. At the conclusion of the research, the approved sources for the research were confirmed so that the topic could be addressed to the extent possible to achieve the goals from which it started.